Eksplorasi pohon induk dan koleksi materi genetik bidara laut (Strychnos lucida R Brown) populasi Taman Nasional Bali Barat (Characteristic of Seed Trees and Variation of Seedling Growth Among Seed Trees of Strychnos lucida R Brown from population of West Bali National Park) - Anita Apriliani Dwi Rahayu; Krisnawati Krisnawati (Balai Penelitian Dan Pengembangan Teknologi Hasil Hutan Bukan Kayu, 2019)
As a raw material for traditional medicine in Java and West Nusa Tenggara, almost all part of Strychnos lucida plants is believed that it is potential for medicine. For instance, the seeds and the wood of this plant are used as malarial, diarrhoea and muscle pain drugs. Considering a potential of S. lucida as a raw material for medicine, the propagation activity is important to prevent the extinction of this species in the future. Exploration of this study was started with determining seed trees as a source of genetic materials of S. lucida, fruit collection, and seedlings nursery. Collection of genetic materials was purposed to be an early step of the improvement of S. lucida. Exploration of seed trees used survey method and purposive sampling method is used to decide the location of seed trees. The result was the number of seeds that collected from 53 seed trees at 137.68 seeds. From germination process, it decided 30 seed trees which high of the percentage of sprouts. Ten months after weaning, the average of the percentage of seedlings at 98.22%, the average of height and diameter of seedlings of S. lucida at 14.22 cm and 2.03 mm respectively.